2016
DOI: 10.1039/c6ra19876g
|View full text |Cite
|
Sign up to set email alerts
|

Electrospun hematite nanofiber/mesoporous silica core/shell nanomaterials as an efficient adsorbent for heavy metals

Abstract: Functionalized nanomaterials hold tremendous promise for water treatment because their high surface area makes them ideal sorbents for pollutants like heavy metal ions that are pervasive in global water supplies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…Among the various materials used for chromium removal, nanoparticles have been the most common, either using just the core nanoparticles [9,[40][41][42][43][44][45][46], nanoparticles with functionalization [35,[47][48][49], or modified nanoparticles incorporated on substrates [36,50]. Other type of materials have been used, such as nanocomposites [37,51,52], nanofibers [38] and carbon nanotubes [39]. In present review, nanomaterials like zero-valent iorn nanoparticels (nZVI) were not found.…”
Section: Type Of Materialsmentioning
confidence: 90%
See 4 more Smart Citations
“…Among the various materials used for chromium removal, nanoparticles have been the most common, either using just the core nanoparticles [9,[40][41][42][43][44][45][46], nanoparticles with functionalization [35,[47][48][49], or modified nanoparticles incorporated on substrates [36,50]. Other type of materials have been used, such as nanocomposites [37,51,52], nanofibers [38] and carbon nanotubes [39]. In present review, nanomaterials like zero-valent iorn nanoparticels (nZVI) were not found.…”
Section: Type Of Materialsmentioning
confidence: 90%
“…Numerous studies have been published on chromium sorption in aqueous phase using various materials and in particular synthetic nanomaterials [9,[35][36][37][38][39]. To select the articles For each selected article, it was extracted the information related to the parameters considered relevant in sorption [7][8][9]: name and nature of the sorbent, mass of the sorbent with respect to the water volume, type of water used in the experiment, type of experiment (single or other contaminants besides chromium), pH, temperature, contact time between the sorbent and the solution, initial concentration of chromium, chromium species initially present in solution, and removal efficiency.…”
Section: Materials and Methodologymentioning
confidence: 99%
See 3 more Smart Citations